Pengaruh Efektivitas Pengendalian Internal, Kesesuaian Kompensasi Dan Budaya Etis Organisasi Terhadap Kecurangan Akuntansi Pada Pemerintahan Kabupaten Barru - Ilyas Ali; Mursalim Mursalim; Abbas Selong (Journal on Education, 2023)
This study aims to examine the suitability of compensation and organizational ethical culture against accounting fraud in the Barru district government. The data in this study were obtained from employees who were willing to be respondents. This study used primary data by conducting direct research in the field by giving questionnaires/question sheets to 53 respondents. The data analysis method used is multiple linear regression analysis. The results showed that: partially, the variables of Internal Control Effectiveness, Appropriateness of Compensation and Organizational Ethical Culture have a positive and significant effect on Accounting Fraud in the Government of Barru Regency.